2019
DOI: 10.1016/j.pmrj.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Measurements of the Prearthritic Hip Between Plain Radiography and Computed Tomography

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Scarce literature has specifically addressed the interchangeability of hip parameters between XR and CT. Similar angle measurements were reported by some authors between these modalities, with CT measurements correlating well with some radiographic parameters, 46 namely, acetabular inclination, lateral center-edge angle (L-CEA), and α angles (intermodality reliability, as well as intra-and interrater reliability, of both modalities showed excellent performance 46 ). However, this was only achievable if a standardized procedure was used.…”
Section: Plain Radiographs and Ctsupporting
confidence: 83%
See 1 more Smart Citation
“…Scarce literature has specifically addressed the interchangeability of hip parameters between XR and CT. Similar angle measurements were reported by some authors between these modalities, with CT measurements correlating well with some radiographic parameters, 46 namely, acetabular inclination, lateral center-edge angle (L-CEA), and α angles (intermodality reliability, as well as intra-and interrater reliability, of both modalities showed excellent performance 46 ). However, this was only achievable if a standardized procedure was used.…”
Section: Plain Radiographs and Ctsupporting
confidence: 83%
“…47 These results complement other studies showing consistencies associated with CT-facilitated assessments of the pre-arthritic hip. 12,46 However, other authors found that measurement of the Wiberg center-edge angle (W-CEA) consistently increased on CT in accordance with clinical etiology (W-CEA was larger by a mean of 4.9-5.1 degrees on CT in hips with DDH), emphasizing the need for standardization and validation of CT-based measurements. 44…”
Section: Plain Radiographs and Ctmentioning
confidence: 99%
“…An AP pelvic radiograph should be the initial examination for assessing acetabular coverage, although cross-sectional imaging may be also used to assess coverage, providing similar measurements for most parameters [18,27,[53][54][55]. Conflicting reports exist regarding the effect of pelvic positioning on radiographic parameters of coverage [28,[56][57][58], although tilt and rotation seem to mainly influence radiographic signs of acetabular retroversion [9, 22,…”
Section: Statementmentioning
confidence: 99%
“…The intraobserver ICC was in line with a study by Air et al, 12 which reported values of 0.83 [CI: 0.70-0.90] for CEA (vs. 0.84 present study) and of 0.75 [CI: 0.55-0.86] for AI (vs. 0.77). The interobserver ICC was within the values reported in the literature, knowing that, in patients with hip disorders, the interobserver ICC can vary from 0.78 [CI: 0.69-0.85] to 0.95 [CI: 0.91-0.98] for CEA (vs. 0.77), from 0.87 [CI: 0.80-0.92] to 0.98 [CI: 0.93-0.99] for AI (vs. 0.56) and from 0.68 [CI: 0.55-0.78] to 0.95 [CI: 0.81-0.99] for AV(vs. 0.85) 10,12,45. The interobserver ICC reported in this study might be in the literature lower range for several reasons.…”
mentioning
confidence: 51%
“…In addition, MR and CT have similar diagnostic power, providing accurate bone models 8,9 and morphometric measurements of the hip which correlate well with each other 10,11 and with radiography-based measurements. 12,13 MR images are commonly used for diagnostic purposes in orthopedic care 14,15 due to their ability to expose defects in periarticular and intraarticular soft tissues. 16 However, the nonselective visualization of bone on common MR images complicates both bone modeling and the measurement of diagnostic parameters as extra care needs to be taken to discriminate bone from soft tissues such as the labrum 13 or ligaments.…”
Section: Introductionmentioning
confidence: 99%